THE INVESTIGATION OF SITUATIONAL LEADERSHIP, AND WORK MOTIVATION ON KINDERGARDEN TEACHER PERFORMANCE - Yayan MUDIYANTUN (Journal of Education and Leadership in Education, 2019)
The purpose of this study was to investigate the influence of the principal's situational leadership on teacher performance; the influence of work motivation on teacher performance; and the influence of the principal's situational leadership on work motivation. The research employed a causal survey research and path analysis technique. The sample of 103 kindergarten teachers of Tanggerang regency was taken by using proportional random sampling. The results have shown that 1) Path coefficient value of the principal’s situational leadership and the teacher performance is 0.440 with the probability significance value ρx3x1 = 0.000. It means that the principal’s situational leadership has a significant effect on teacher performance. 2) Path coefficient value of work motivation and the teacher Performance is 0.166 with the probability significance value ρx3x1 = 0.005. It indicates that work motivation has a significant effect on teacher performance. 3) Path coefficient value of situational leadership and teacher work motivation is 0,598 with probability significance value ρx3x1 = 0.000. It implies that the principal’s situational leadership has a significant effect on work motivation. Based on the research findings, it can be inferred that leadership style has a major role to develop work motivation and performance that have a positive impact on the quality of individuals in an organization